Fatal antiphospholipid syndrome following endoscopic transnasal-transsphenoidal surgery for a pituitary tumor: A case report. Issue 1 (January 2017) - Li, Chiao-Zhu; Li, Chiao-Ching; Hsieh, Chih-Chuan; Lin, Meng-Chi; Hueng, Dueng-Yuan; Liu, Feng-Chen; Chen, Yuan-Hao
Abstract: Introduction: The fatal type of antiphospholipid syndrome is a rare but life-threating condition. It may be triggered by surgery or infection. Endoscopic transnasal-transsphenoidal surgery is a common procedure for pituitary tumor. We report a catastrophic case of a young woman died of fatal antiphospholipid syndrome following endoscopic transnasal-transsphenoidal surgery. Methods and Result: A 31-year-old woman of a history of stroke received endoscopic transnasal-transsphenoidal surgery for a pituitary tumor. The whole procedure was smooth. However, the patient suffered from acute delirium on postoperative day 4. Then, her consciousness became comatose state rapidly with dilatation of pupils. Urgent magnetic resonance imaging of brain demonstrated multiple acute lacunar infarcts. The positive antiphosphoipid antibody and severe thrombocytopenia were also noted. Fatal antiphospholipid syndrome was diagnosed. Plasma exchange, corticosteroids, anticoagulant agent were prescribed. The hemodynamic condition was gradually stable. However, the consciousness was still in deep coma. The patient died of organ donation 2 months later. Conclusion: If patients have a history of cerebral stroke in their early life, such as a young stroke, the APS and higher risk of developing fatal APS after major surgery should be considered. The optimal management of APS remains controversial. The best treatment strategies are only early diagnosis and aggressive therapies combing of anticoagulant, corticosteroid, and plasma exchange. The intravenous immunoglobulin is prescribed for patients with refractory APS.